2012
DOI: 10.1186/1755-8794-5-63
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and multiple gene expression variables in survival analysis of breast cancer: Analysis with the hypertabastic survival model

Abstract: BackgroundWe explore the benefits of applying a new proportional hazard model to analyze survival of breast cancer patients. As a parametric model, the hypertabastic survival model offers a closer fit to experimental data than Cox regression, and furthermore provides explicit survival and hazard functions which can be used as additional tools in the survival analysis. In addition, one of our main concerns is utilization of multiple gene expression variables. Our analysis treats the important issue of interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A total of 27,532 U.S. melanoma patients of whom 15,527 were males and 12,005 were females. The Hypertabastic Accelerated Failure Time model [21][22][23][24][25][26] was used to analyze the survival probabilities in patients with cutaneous or mucosal melanoma.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 27,532 U.S. melanoma patients of whom 15,527 were males and 12,005 were females. The Hypertabastic Accelerated Failure Time model [21][22][23][24][25][26] was used to analyze the survival probabilities in patients with cutaneous or mucosal melanoma.…”
Section: Methodsmentioning
confidence: 99%
“…Van et al [8] used the data as a validation set for the seventy gene signature (70G). Tabatabai et al [9] studied the effect of 70G, core serum response signature correlation (CSR) and ErbB2+ correlation (CERBB) on survival using the hypertabastic model. Chang et al [10] identified a set of "core serum response" (CSR) genes.…”
Section: Data Description and Analysis Methodsmentioning
confidence: 99%
“…The hypertabastic distribution has been used in biomedical applications such as studies of survival of cancer patients [14,15]. An important advantage of the hypertabastic hazard function compared to other such distributions (e.g.…”
Section: Hypertabastic Survival Modelmentioning
confidence: 99%